2021
DOI: 10.1101/2021.08.05.455040
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Virucidal activity of CPC-containing oral rinses against SARS-CoV-2 variants and are active in the presence of human saliva

Abstract: The role of human saliva in aerosol-based transmission of SARS-CoV-2 has highlighted the need to understand the potential of oral hygiene products to inactivate the virus. Here we examined the efficacy of mouthwashes containing cetylpyridinium chloride (CPC) or chlorhexidine (CHX) in inactivating SARS-CoV-2. After 30 seconds contact under standard aqueous conditions CPC mouthwashes achieved a ≥4.0log10 PFU/mLreduction in SARS-CoV-2 (USA-WA1/2020) titres whereas comparable products containing CHX achieved <2… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 27 publications
(31 reference statements)
0
5
0
Order By: Relevance
“…50 One preprint article reported that CHX (0.12%) achieved low, moderate, and high efficacy, depending on the viral strain used. 37 Meister and colleagues 46 reported low efficacy results after a 30-second rinse with a CHX mouthrinse with unknown concentration. Cetylpyridinium chloride (CPC) in vivo virucidal activity was studied in an RCT by Seneviratne and colleagues 22 on a group of 4 hospitalized patients (eTable 4, available online at the end of this article).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
See 2 more Smart Citations
“…50 One preprint article reported that CHX (0.12%) achieved low, moderate, and high efficacy, depending on the viral strain used. 37 Meister and colleagues 46 reported low efficacy results after a 30-second rinse with a CHX mouthrinse with unknown concentration. Cetylpyridinium chloride (CPC) in vivo virucidal activity was studied in an RCT by Seneviratne and colleagues 22 on a group of 4 hospitalized patients (eTable 4, available online at the end of this article).…”
Section: Results Of Individual Studiesmentioning
confidence: 99%
“…Studies included in qualitative synthesis n = 39 Regarding SARS-CoV-2 strains used across in vitro studies, several used well-characterized strains, the most used being USA-WA1/2020. [30][31][32][33][34][35][36][37][38] Four studies used a SARS-CoV-2 strain directly obtained from an infected patient, 39-42 whereas 1 study did not report the strain used. 43 In vitro studies were performed under dirty, [44][45][46][47][48] clean, 30,[32][33][34][35][36][38][39][40]42,43,[49][50][51][52][53][54][55] or both conditions, 37,41,56,57 with the terms dirty and clean referring to the existence of interfering substances.…”
Section: Medline N = 240mentioning
confidence: 99%
See 1 more Smart Citation
“…Formulations including hydrogen peroxide, benzalkonium chloride, dequalinium chloride, chlorhexidine, cetylpyridinium chloride, octenidine dihydrochloride, povidone–iodine, alkaline solutions, ethanol, hexetidine, cyclodextrin, polyaminopropyl biguanide, bioflavonoids, hypochlorous acid, delmopinol, silver nanoparticles, combination surfactants, essential oils, hydroxyapatite, glycyrrhizic acid, and/or sodium fluoride have been assessed. 150 , 154 , 169 , 172 , 174 , 175 , 176 , 177 , 178 , 179 , 180 , 181 , 182 , 183 , 184 , 185 , 186 Efficacy during in vitro or in vivo experiments has yielded variable results. Komine et al 175 did not find efficacy for chlorhexidine.…”
Section: Disinfectants and Topical Mucosal Applicationmentioning
confidence: 99%
“…Others found reduced efficacy for hydrogen peroxide and chlorhexidine. 150 , 177 , 179 , 180 Cetylpyridinium chloride in various dilutions inactivates virus, and the mechanism of action in part appears to be related to the interruption of the Spike protein/receptor complex. 150 , 169 , 186 The degree of product dilution has a considerable impact.…”
Section: Disinfectants and Topical Mucosal Applicationmentioning
confidence: 99%